(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
This article extensively explores marriage norms in ancient India, focusing on women’s agency. It begins by dissecting the concept of marriage and its variations in ancient India and sheds light on its significance from women’s viewpoints. It scrutinises the roles of women within the institution, including debates surrounding the age of marriage, the qualities sought in brides, and the complexities of partner selection including the prohibited degrees of marriage. The paper delves into her roles in marriage rituals as well as post-marital positions. Contentious issues like divorce and remarriage of women have also been touched. Overall, this article aims to uncover obscure aspects of women’s autonomy within marriage, analysing their roles and representations across all facets. By examining evolving Hindu marriage norms throughout the Vedic, Puranic and Smriti periods, it emphasizes the need for a refined understanding of women’s agency. The paper seeks to contribute to a comprehensive understanding of marriage in ancient India, particularly from the perspective of women’s representations, urging readers to reconsider conventional narratives. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 69(1), 2024, pp. 1-32